2003
DOI: 10.1354/vp.40-4-445
|View full text |Cite
|
Sign up to set email alerts
|

Parapoxvirus Infection in Harbor Seals (Phoca vitulina) from the German North Sea

Abstract: In the summer of 2000, proliferative lesions of the skin and oral mucosa were observed in 26 young harbor seals (Phoca vitulina) from a rehabilitation center in Schleswig-Holstein, Germany. Verrucose, roundish nodules, approximately 1-2 cm in diameter, were presented in the oral cavity, especially on the tongue. Some animals developed similarly sized spherical dermal elevations with ulceration on flippers, chest, neck, and perineum. Necropsy of one animal showed multifocal, verrucose nodules in the oral cavity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 27 publications
(56 reference statements)
1
44
0
2
Order By: Relevance
“…13). Many of the neoplastic cells had large irregular eosinophilic cytoplasmic inclusion bodies and with electron microscopy discrete viral particles compatible with a parapoxvirus (Muller et al, 2003;Nollens et al, 2006). This tumor was classified as a well-differentiated squamous cell papilloma associated with a parapoxvirus.…”
Section: Model Results For Pupsmentioning
confidence: 95%
“…13). Many of the neoplastic cells had large irregular eosinophilic cytoplasmic inclusion bodies and with electron microscopy discrete viral particles compatible with a parapoxvirus (Muller et al, 2003;Nollens et al, 2006). This tumor was classified as a well-differentiated squamous cell papilloma associated with a parapoxvirus.…”
Section: Model Results For Pupsmentioning
confidence: 95%
“…Poxvirus has been well documented in seals and sea lions (Wilson et al 1969;Wilson et al 1972;Becher et al 2002;Muller et al 2003), which occupy the same coastal areas as bottlenose dolphins in California, and is known to occur in cetaceans (Flom and Hoek 1979;Geraci et al 1979;Van Bressem et al 1993Brownell et al 2007). The coastal environment in California, and in Monterey Bay in particular, is of concern because of high contaminant loads and general levels of pollutants (Hartwell 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A number of other viruses have been identified as tentative species of parapoxvirus, but are not recognized as official members of the genus; these include seal poxvirus [13], chamois contagious ecthyma and Auzdyk disease virus (both of which affect camels) [7,14]. Parapoxviruses affecting sea lions [15], harbor seals (Phoca vitulina) in the German North Sea [16], gray seals (Halichoerus grypus) and Weddell seals (Leptonychotes weddellii) in Antarctica [17] have also been reported. Studies have shown that the Weddell seal virus is genetically related to parapoxvirus of gray seal (Halichoerus grypus) and harbor seal (Phoca vitulina) under the tentative seal parapoxvirus species [17].…”
Section: Etiology and Taxonomic Statusmentioning
confidence: 99%